Excess Return of Active Management in Investment Companies - Mohammad A. Mazar Yazdi; Shahnaz Mashayekh (مطالعات تجربی حسابداری مالی, 2003)
The Performance Evaluation Models that developed from Middle of 1960s was used in many researches. Between three Models that were developed by William Sharp, Jack Treynor and Michael Jensen, many researches used differential excess return of Jensen Model. Some of researches that were previously done showed that investment company with active management usually obtain gross excess return. However this return almost was not important and after deduction of operating expense would be eliminated or negative. This article shows results of research that investigate the performance of 14 Iranian investment companies between 1374 -1380. Sharp and Jensen models were used respectively in determining portfolio Risk and Return and evaluating performance. This research tested eight hypotheses. The result demonstrates 26.9 percent average gross excess return. This excess return will become 25.8 percent after deducting operating expenses. Shortening the calculation Periods almost confirm above results. In summary, the results of testing eight hypotheses demonstrate that active management in Iranian investment companies for Marketable securities performed better than passive management and could obtain important excess return. Of course investment holding companies had a much   better performance than mutual fund.